Peningkatan Aktivitas dan Prestasi Belajar Matematika Melalui Metode Modelling The Way pada Siswa Kelas IX SMP - Indra Kurniawan (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2016)
The purpose of this study is to improve SMP students’ activity and learning achievement, in mathematics, with the application of the Modeling the Way method, during the 2012/2013 academic year. This research is a classroom action research (PTK) that is conducted in two cycles. Each cycle consists of preparation, action, observation, and reflection. Cycle I and Cycle II are executed within three meetings each. Subjects are IXF grade students of SMP N 1 Ceper amounting to 24 students consisting of  9 male and 15 female students. The data was taken by increased observation of students’ activities during the learning process, while their achievement was measured by evaluating them in the form of tests. The results showed that: (1) The students’ activities have increased from the first cycle to the second cycle. (2) The students’ learning outcomes have also risen, as shown by an increase in the cycle’s final test results. The average final test scores, from cycle I to cycle II, has risen from 71.04% into 79.17%. While the minimum percentage of completeness increased from 70.83% to 87.5%. The test results of the second cycle have reached the indicator of the success that has been established when 80% of students reached the Value Minimum Criteria for completeness (KKM), which is 68. From the results above, it can be concluded that the application of the Modelling The Way method can increase the activity and learning achievement of IX SMP students during the 2012/2013 academic year. Keywords: Modeling the Way method, activity, and achievement